Risk Factors for HIV incidence in Men Who Have Sex With Men (MSM) and Viral Load Status in Indonesia: Literature Review - Pratami, Yunita; Januar Sitorus, Rico; Najmah, Najmah (Rifa'Institute, 2025)
Introduction: HIV incidence among Men who have Sex with Men (MSM) continues to rise and is influenced by behavioral, social, and health-related factors. MSM remain a high-risk group due to risky sexual practices and barriers to accessing healthcare. Objective: This study aims to identify and analyze the key behavioral, demographic, social, and health determinants contributing to HIV infection among MSM, as well as to provide evidence-based recommendations for prevention strategies. Methods: This study employed a systematic literature review of 15 articles that met inclusion criteria from PubMed, PMC, and Google Scholar. Screening followed the PRISMA approach, and findings were synthesized qualitatively based on behavioral, demographic, social, and health characteristics. Results and Discussion: Risky sexual behaviors including unprotected anal/oral intercourse, multiple sexual partners, and receptive sexual positioning were identified as dominant contributors to HIV infection among MSM. Demographic factors (productive age, low education), social-psychological factors (stigma, discrimination, lack of family support), and sexually transmitted infections further increased vulnerability. Poor adherence to antiretroviral therapy resulted in unsuppressed viral load, heightening transmission risk. Conclusion: Comprehensive prevention strategies are essential, including behavioral education, MSM-inclusive healthcare services, stigma reduction, and strengthened ART adherence to reduce HIV transmission among MSM.